The Malaysian Cataract Surgery Registry. Issue 4 (July 2015) - Salowi, Mohamad Aziz; Goh, Pik-Pin; Lee, Ming-Yueh; Adnan, Tassha Hilda; Ismail, Mariam
<x xml:space="preserve">Abstract</x> Purpose To investigate the change in the profile of patients who had cataract surgery at Ministry of Health (MOH) hospitals in Malaysia. Design Secondary analysis on Malaysian Cataract Surgery Registry data. Methods The Malaysian Cataract Surgery Registry, a MOH-initiated registry, collects data on patients who had cataract surgery at the 36 MOH ophthalmology departments including demography, causes of cataract, systemic and ocular comorbidity, preoperative visual acuity (VA), operative details, and postoperative outcomes. This article reviews data on patient profiles from 2002 to 2004 and 2007 to 2011. Results The coverage of cataract surgery was 91.5% (171, 482/185, 388). Mean patient age was 64.5 years, and 51.6% were women. A high proportion of patients had hypertension (48.9%), diabetes mellitus (37.1%), and diabetic retinopathy (10.7%). Most had senile cataract (93.4%) and one third had second eye surgery. Most patients (82.0%) had preoperative unaided VA of worse than 6/12. Eyes presenting with unaided VA of worse than 3/60 decreased from 62.6% in 2002 to 47.7% in 2011, whereas those with 6/18 to 3/60 increased from 35.2% to 48.5% (P < 0.001). Patients who had extracapsular cataract extraction had worse preoperative VA than those who had phacoemulsification (81.3% vs 40% had vision worse than 3/60). Conclusions The obvious change in patient profiles was the decreasing number of eyes presenting with worse than 3/60 vision. Compared with developed countries, patients who had cataract surgery at MOH hospitals in Malaysia were younger and had higher associations with diabetes mellitus and diabetic retinopathy.